(untitled) (Raparin Journal of Humanities (RJH), 2021)
The ceasefire between the Kurdistan Democratic Party-Iraq and the Baathist government in 1974 came to an end, and fighting between the two sides resumed. The war lasted another eleven months. At the start of the war, a group of writers and artists reached out to areas controlled by the revolution and formed organizations. Many of them were members of the Kurdish Writers’ Union and They were able to issue 12 of their magazine, but the writers’ union was established in Baghdad, not in the revolution. After the collapse of 1975 and the resumption of the new revolution in the areas under Peshmerga control, especially in the early 1980s, for the first time in the battlefields of resistance and defense in Kurdistan, a special organization for writers and writers was established, called the Kurdistan Writers’ Union.. The Kurdistan Writers’ Union’s establishment and activities were addressed in this study, and the reason for its cancellation was clarified. The first section of the study, which was split into two sections, focused on the efficiency and explanations for the organization’s formation. The publication chosen by the Kurdistan Writers’ Union through a series of criteria is the subject of the second part of the study.